PENGARUH LOKASI DAN WORD OF MOUTH TERHADAP KEPUTUSAN PENGGUNAAN JASA PERCETAKAN CV GLOBAL KREASI MEDIA PADA MASYARAKAT KOTA PASURUAN - Ludfiyah, Wahyu; Fibriyani, Vita; Akramiah, Nurul (STIE PENA, 2024)
Technological developments are increasingly being used by more and more people, one of which is printing technology which is simpler, faster and more sophisticated. Digital printing is a modern printing technology used to produce digital images that are processed by a computer onto the surface of the material. In this case, the researcher wants to know the influence of location and word of mouth on the decision to use CV Global Kreasi Media printing services among the people of Pasuruan City. Where this research is aimed at old customers and new customers totaling 75 respondents. Using non-probability sampling techniques with simple random sampling techniques. The analysis used was multiple linear regression analysis. Based on the results of the analysis, it is known that there is an influence of location and word of mouth on the decision to use services with a coefficient of determination of 51.1% while the remaining 48.9% is explained by other factors not involved in this research. The research results show that location has a positive and significant effect on the decision to use services with a regression coefficient of sig 0.006 < 0.05 and Word of Mouth has a positive and significant effect on the decision to use services with a sig value of 0.001 < 0.05. Keywords: Location, Word Of Mouth, Usage Decision